TINJAUAN MAQASID SYARI’AH TENTANG TAKLIK TALAK DALAM PERNIKAHAN DI INDONESIA - Haq, Izharul; Shuhufi, Muhammad; Patimah (MADDIKA : Journal of Islamic Family Law, 2024)
This paper aims to examine the practice of taklik talak in marriage in Indonesia from a maqasid sharia perspective.  Taklik talak is an agreement made by the husband after the marriage contract, in which he promises to impose talak if he violates certain conditions that have been agreed upon.  This practice has long been implemented in the Islamic family law tradition in Indonesia, with the aim of protecting the wife's rights and ensuring the husband's responsibilities. In this study, the concept of maqasid sharia is used as an analytical framework to assess whether taklik talak is in line with the main objectives of sharia, namely protecting religion (hifz ad-din), soul (hifz an-nafs), reason (hifz al-'aql), descendants  (hifz an-nasl), and wealth (hifz al-mal).  Analysis shows that taklik talak functions as a protection mechanism for wives in marriage, especially in ensuring that husbands fulfill their responsibilities, such as providing a living and maintaining household harmony.  This is in line with the principles of maqasid sharia, especially in maintaining justice, protecting women's rights, and preventing injustice in the household. However, the implementation of taklik talak also presents challenges, especially in the aspect of public understanding and its legal implementation.  Thus, a holistic approach is needed to increase legal awareness and provide clear guidance regarding taklik talak so that this practice remains relevant and beneficial for married couples in Indonesia